2007
DOI: 10.1091/mbc.e06-09-0876
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Localization of Calpain 2 during Neutrophil Chemotaxis

Abstract: Chemoattractants induce neutrophil polarization through localized polymerization of F-actin at the leading edge. The suppression of rear and lateral protrusions is required for efficient chemotaxis and involves the temporal and spatial segregation of signaling molecules. We have previously shown that the intracellular calcium-dependent protease calpain is required for cell migration and is involved in regulating neutrophil chemotaxis. Here, we show that primary neutrophils and neutrophil-like HL-60 cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 62 publications
2
44
1
Order By: Relevance
“…Syndecan-translocation to lipid rafts plays a role in cell migration (39). Lipid rafts are known to serve as platforms for molecules (42), and translocation of molecules, such as ICAM-1 (30), calpain (32), and integrins (25), to lipid rafts is necessary to activate cell migration. We demonstrated that Epac increased translocation of syndecan-2 to lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syndecan-translocation to lipid rafts plays a role in cell migration (39). Lipid rafts are known to serve as platforms for molecules (42), and translocation of molecules, such as ICAM-1 (30), calpain (32), and integrins (25), to lipid rafts is necessary to activate cell migration. We demonstrated that Epac increased translocation of syndecan-2 to lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…2B) or the expression of the other HSPGs (data not shown). Since syndecan is known to translocate to lipid rafts (40), which serve as platforms for molecules involved in cell migration (26,30,32), we hypothesized that such large particle size indicates accumulation of syndecan-2 in lipid rafts. Indeed, immunocytochemistry showed that both Epac agonist and Epac1 overexpression increased colocalization of syndecan-2 with lipid rafts.…”
Section: Epac Increases Migration In Melanomamentioning
confidence: 99%
“…HL-60 cells (UCSF tissue culture facility) were cultured and differentiated as previously described (Nuzzi et al, 2007b). Phoenix viral packaging cells were transiently transfected by calcium-phosphate precipitation (Nuzzi et al, 2007a).…”
Section: Cell Culture and Retroviral Infectionmentioning
confidence: 99%
“…Primary human neutrophils, undifferentiated and differentiated HL-60 cells, and HEK 293 cells were lysed (Nuzzi et al, 2007b), samples were clarified by centrifugation, and protein concentration was determined using a bicinchoninic acid (BCA) protein assay (Pierce, Rockford, IL). Equal amounts of total protein were denatured in SDS sample buffer, resolved on 4 -20% gradient Representative images of neutrophils demonstrate localization of endogenous PIPKI␥ (P␥; C) and active RhoA (rhotekin; D) to the cell rear upon fMLP stimulation.…”
Section: Protein Extraction Antibodies and Immunoblotsmentioning
confidence: 99%
“…During neutrophil migration, actin microfi lament polymerization leads to the extension of membrane projections (i.e., protrusions) at the leading edge, including fi lopodia and lamellipodia, which are required for directional migration. In the case of neutrophils, exposure to a chemoattractant gradient induces the rapid enrichment of the protease calpain 2 at the leading edge where it colocalizes with F-actin (Nuzzi et al, 2007). Localization of the protease at the leading edge seems to be causal for neutrophil migration because the expression of an inactive protease variant (Calpain PD) generates multiple lamellipodia surrounding neutrophils without a defi ned leading edge and prevents effi cient chemotaxis (Nuzzi et al, 2007).…”
Section: Role Of Calpain In Polarization During Cell Migrationmentioning
confidence: 99%